Assessment of the herpes zoster risk among renal transplant recipients administered the influenza vaccine - Cheng, Tzu-Ming; Chen, Yin-She; Wei, Kai‐Che; Chang, Yu‐Chia; Huang, Yu‐Tung; Chen, Chien-Liang (Vaccine, 2024)
Reactivation of the latent varicella-zoster virus can cause herpes zoster (HZ) infection, and renal transplant recipients undergoing immunosuppressive therapy are particularly susceptible to this condition. This study aims to evaluate the potential increase in HZ incidence following influenza vaccination among this specific patient population. This study was a population-based, retrospective, self-controlled case series. Data were retrieved from Taiwan’s National Health Insurance Research Database spanning the years 2008 to 2017. Patients diagnosed with HZ within a 6-month period before and after receiving the influenza vaccine were eligible for inclusion. Two distinct time intervals were defined for analysis: the initial 15 days and 30 days following vaccination were categorized as risk intervals, while all other periods served as control intervals. Incidence rate ratios (IRRs) were computed to compare HZ incidence during the risk intervals with that during the control intervals. This study encompassed a cohort of 4,222 renal transplant recipients who had received the influenza vaccine. Among this group, 67 recipients were subsequently diagnosed with HZ. The IRR during both the initial 15 days (IRR = 0.63; 95 % CI, 0.23–1.89) and the first 30 days (IRR = 1.50; 95 % CI, 0.71–3.16) following influenza vaccination did not demonstrate a statistically significant increase when compared to the post-exposure observation times. Comparable results were also observed when comparing these IRR values to the pre-exposure observation times. The subgroup analysis, stratified by age, sex, and underlying medical conditions (including cancer and autoimmune diseases), revealed that the IRRs did not exhibit statistically significant differences. No significant association between the influenza vaccine and an elevated risk of HZ was detected. The administration of annual influenza vaccines appears to be a reasonable practice for renal transplant recipients.